Intelligence beliefs, goal orientations and children's academic achievement: does the children's gender matter?. Issue 1 (2nd January 2019) - Diaconu-Gherasim, Loredana R.; Tepordei, Ana-Maria; Mairean, Cornelia; Rusu, Andrei
Abstract: This study evaluated how gender is related to children's intelligence beliefs, goal orientations and academic achievement and whether there are gender differences in how intelligence beliefs and goal orientations are related to academic achievement. The participants, 362 seventh grade students (55.8% girls; M age = 13.20, SD = .57 years), completed measures regarding their intelligence beliefs and goal orientations at the beginning of the second semester and the grades were collected at the end of the semester. Girls reported higher scores on incremental belief, mastery goal and higher achievement but lower levels of performance avoidance compared to boys. The relations between intelligence beliefs and academic achievement were fully mediated by both performance goals. Further, there were no gender differences in the associations among intelligence beliefs, goal orientations and achievement. The findings reveal that goal orientations are a mechanism that might explain why intelligence beliefs are linked with academic achievement in early adolescence.